THE USE OF MIND MAPPING AND FLOW CHARTING IN TEACHING ENGLISH WRITING SKILL OF INTROVERTED STUDENTS - Daniar Sofeny; Irmayan Irmayan (E-LINK JOURNAL, 2018)
Introverted student is a type of student who has a personality related to the world in his own mind. Based on some researches results, they showed that the type of introverted students is getting lower in achievement compared to the extroverted type. For this reason, the researchers tried to apply the techniques in order to improve the introverted students’ achievement in learning English. The researchers focused on the writing skill. So, the writing techniques, namely Mind Mapping and Flow Charting are used in this research to improve their writing skill. This study was aimed to know the effectiveness of using Mind Mapping in teaching English writing skill of introverted Students, to know the effectiveness of using Flow Charting in teaching English writing skill of introverted Students, and to determine the better technique between Mind Mapping and Flow Charting in teaching English Writing Skill of Introverted Students.  The research technique used was descriptive comparative with a quantitative approach. The results of this study indicated that both techniques are equally effective. The results of the average writing test for the use of Mind Mapping techniques is 56.5, while for the use of Flow Charting techniques is 49.6. From the results of the average score, it can be concluded that flow charting techniques are more effectively used to improve the students writing skills with introverted types.